PENGEMBANGAN MUSEUM VIRTUAL PRAAKSARA INDONESIA SEBAGAI MEDIA PEMBELAJARAN MAHASISWA PRODI PENDIDIKAN SEJARAH FKIP UNTAN - Robbani, Muhammad Iqbal; Chalimi, Ika Rahmatika; Mirzachaerulsyah, Edwin (Jurnal Pendidikan Sejarah Indonesia, 2024)
Abstract: This research aims to develop the Indonesian Prehistoric Virtual Museum as a learning medium for students of the History Education Study Program at FKIP UNTAN. Geographical barriers are one of the reasons why the development of this virtual museum is necessary. This study employs a research and development method that adapts from the Allesi and Trollip model, consisting of the stages of Product Planning, Product Design, Product Development, Product Validation, and Product Testing. Based on the analysis of needs, students require an interactive platform that facilitates access to various types of Indonesian prehistoric collections. Adjustments to the design according to user needs resulted in a virtual museum design that includes features such as: Multiplayer, 3D Object Display, Voice Chat, Text Chat, Character Customization, Profile Customization, Graphic Settings, Audio Settings, Audio Description, Third Person POV, First Person POV, Quiz, and Puzzle. Feasibility testing was conducted through expert validation and group trials with positive results: Media Expert 81%, Content Expert 80 percent, Small Group Test 82 percent, and Large Group Test 81 percent. Based on the results of expert validation and group trials, this museum meets the feasibility requirements as a medium that facilitates access and has features aligned with user needs. Abstrak: Penelitian ini bertujuan untuk mengembangkan Museum Virtual Praaksara Indonesia sebagai media pembelajaran untuk mahasiswa Prodi Pendididkan Sejarah FKIP UNTAN. Hambatan geografis menjadi salah satu alasan pengembangan museum virtual ini perlu dilakukan. Penelitian ini menggunakan metode penelitian dan pengembangan yang mengadaptasi dari model Allesi and Trollip, yang terdiri dari tahapan Perencanaan Produk, Desain Produk, Pengembangan Produk, Validasi Produk, Uji coba Produk. Berdasarkan hasil analisis kebutuhan mahasiswa membutuhkan platform interaktif yang memudahkan akses ke berbagai jenis koleksi praaksara Indonesia. Penyesuaian desain terhadap kebutuhan pengguna memperoleh desain museum virtual yange memiliki fitur: Multiplayer, 3D Object Display, Voice Chat, Text Chat, Character Customization, Profile Customization, Graphic Settings, Audio Settings, Audio Settings, Audio Description, Third Person POV, First Person POV, Quiz, dan puzzle. Uji kelayakan dilakukan melalui validasi ahli dan uji coba kelompok dengan hasil positif: Ahli Media 81 persen, Ahli Materi 80 persen, Uji Kelompok Kecil 82 persen, dan Uji Kelompok Besar 81 persen. Berdasarkan hasil validasi ahli dan uji coba kelompok museum ini memenuhi kelayakan sebagai media yang memudahkan akses dan memiliki fitur-fitur sesuai dengan kebutuhan pengguna.